PENGARUH KEMAMPUAN MEMBACA PEMAHAMAN DAN PENGUASAAN KOSAKATA TERHADAP KETERAMPILAN MENULIS ARGUMENTASI PADA PESERTA DIDIK SMA DI DEPOK - Nur Irwansyah; Azhari Ikhwati (Universitas PGRI Semarang, 2016)
This study generally aims to determine student’s reading comprehension, vocabulary mastery of the students, and the ability to write arguments class XI High School in Depok, particularly SMA Tugu Ibu 1 Depok, while specifically to get a picture of whether there is influence between reading comprehension student’s ability to write arguments, obtain information whether there is influence between students' vocabulary mastery of the ability to write arguments, get a picture there is influence reading comprehension and vocabulary skills of students to write arguments.This study is using a survey method with correlation technique based on a simple regression analysis and multiple regression analysis. The population in this study amounted to 248 high school students of class XI Tugu Ibu 1 Depok Academic Year 2013/2014, which used a sample of 150 students. Data collection techniques using a multiple-choice test to determine the level of reading comprehension, vocabulary level, and essay tests to measure student’s ability to write arguments. Instrument trials conducted to 43 respondents. The validity test is using Point Biserial correlation technique, while the reliability test using the formula KR-20 (Kuder Richardson). Testing requirements analysis include normality test, heteroskedastisiti, multikolineariti test, and test the regression equation fits tuna. Based on the research results can be obtained the following conclusions : (1) ability to significantly influence reading comprehension of written argumentation skills , (2) There is no significant influence of the vocabulary mastery of argumentation writing skills , (3) Variable reading comprehension ability and vocabulary control variables together significantly influential arguments against writing skills as much as 10 percent (R Square = 0.100). It is composed of a variable contribution of reading ability and understanding as much as 5 percent of the control variables vocabulary as much as 5 percent . When calculated as the relative contribution shows that it appears proficiency in reading comprehension and vocabulary accounted for 50 percent . Based thitung value (=6.721, = 2.847, and = -2.585) showed that mass sequentially from the regression coefficient B (multiple regression equation = 74.917 + 0.255 X1 (reading comprehension ability) - 0.337 X2 (mastery vocabulary)) , as well as floor (= 0.000,= 0.005, and = 0.011) showed the first is the ability to read comprehension, secondly vocabulary mastery.Keywords: Learning Reading Comprehension, Vocabulary Mastery, Argumentation Writing Skill